2000
DOI: 10.1523/jneurosci.20-19-07438.2000
|View full text |Cite
|
Sign up to set email alerts
|

Expectation of Pain Enhances Responses to Nonpainful Somatosensory Stimulation in the Anterior Cingulate Cortex and Parietal Operculum/Posterior Insula: an Event-Related Functional Magnetic Resonance Imaging Study

Abstract: Although behavioral studies suggest that pain distress may alter the perception of somatic stimulation, neural correlates underlying such alteration remain to be clarified. The present study was aimed to test the hypothesis that expectation of pain might amplify brain responses to somatosensory stimulation in the anterior cingulate cortex (ACC) and the region including parietal operculum and posterior insula (PO/PI), both of which may play roles in regulating pain-dependent behavior. We compared brain response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
240
2
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 476 publications
(273 citation statements)
references
References 56 publications
(78 reference statements)
28
240
2
3
Order By: Relevance
“…Generally, the influence of internal psychological attitudes on brain activity when facing new events has also been described in other studies: the expectation of pain enhanced responses to nonpainful sensory stimuli in the ACC, posterior insula, and parietal operculum (Sawamoto et al, 2000). Placebo induced an increase of activity in midbrain and prefrontal areas during anticipation of thermal pain .…”
Section: Anatomical and Functional Features Of The Revealed Areassupporting
confidence: 61%
See 1 more Smart Citation
“…Generally, the influence of internal psychological attitudes on brain activity when facing new events has also been described in other studies: the expectation of pain enhanced responses to nonpainful sensory stimuli in the ACC, posterior insula, and parietal operculum (Sawamoto et al, 2000). Placebo induced an increase of activity in midbrain and prefrontal areas during anticipation of thermal pain .…”
Section: Anatomical and Functional Features Of The Revealed Areassupporting
confidence: 61%
“…Chua et al, 1999;Ploghaus et al, 1999;Sawamoto et al, 2000;Phelps et al, 2001;O'Doherty et al, 2002;Ueda et al, 2003;Wager et al, 2004;Simmons et al, 2004;Bermpohl et al, 2006, Nitschke et al, 2006, distinct brain regions comprising dorsolateral and inferior prefrontal cortex, orbitofrontal cortex, cingulate gyrus, insula, amygdala, thalamus, midbrain, and parieto-occipital areas were principal regions of interest involved in the expectation of emotional stimuli with unknown valence.…”
Section: Introductionmentioning
confidence: 99%
“…47), and administration of noxious stimuli alone, such as hind paw formalin injections or footshock, as well as during training, induces c-Fos expression and increased ATP hydrolysis in the ACC (48,49). Studies of both monkeys and humans have shown that the ACC is activated by nociceptive stimuli as well as by the anticipation of pain (50)(51)(52). Recent findings indicate that the ACC is composed of at least two functionally distinct regions.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in prefrontal EEG theta have been linked to activity in the anterior cingulate cortex (ACC), an area that has been implicated in the expectation of pain (Sawamoto et al, 2000) and unpleasant emotional stimuli (Ueda et al, 2003), and has been shown to have prognostic value for determining clinical response to antidepressant medications. In normal subjects, theta activity recorded from prefrontal surface electrodes has been positively correlated with activity in the ACC as measured by magnetoencephalography (MEG; Asada et al, 1999;Ishii, 1999) and positron emission tomography (PET; Pizzagalli et al, 2003).…”
Section: Discussionmentioning
confidence: 99%